Testemonies of faith and hope: the practice of begging (Tempo e Argumento, 2010)
This study deals with the practice of begging in the religious environment, specifically among catholics of the city of Montes Claros, in northern Minas Gerais. Through testimonies, this work intends to reveal the meanings the faithful give to their requests and the direction of their daily demands to the saints, who are taken as intermediaries in solving everyday problems along with God. It resumes the discussion inserted in the Master's dissertation "The demands and popular representations of the political-religious experience in Montes Claros (1996-2004)”. To this end, messages of begging, printed images of saints and testimonies were collected. As a result, it was observed that rationality found in the requests is inherent to the religious universe, where one can believe that whatever may seem impossible may become feasible through the miracle.
Keywords: faith; religion